FACTORS AFFECTING STUDENTS’ FAILURES DUE TO ANXIETY IN LEARNING ENGLISH - Lamhot Naibaho (English Review: Journal of English Education, 2022)
This study aims to determine the factors affecting students' failures due to anxiety in learning English. It was conducted at Universitas Kristen Indonesia, Jakarta, within three months. This study was a descriptive qualitative study with a survey design. The study's respondents consisted of 98 from three parallel classes at UKI. The sampling method in this study uses the cluster sampling method. In this study, a set of questionnaires was used to collect the data. It is used to measure English language anxiety. It has three constructs: communication anxiety, fear of negative assessment, and anxiety in exams, and the English learning anxiety has four constructs: personal reason, teacher attitude, test situation, and teaching procedure. The finding of this study is that English language learners have moderately high speaking skills anxiety and that the level of English language anxiety of English language learners at UKI as a whole in the two English language skills, namely listening and speaking skills, reached a medium-high level. Then it is concluded that teachers emphasize compelling and diverse strategies and techniques of teaching English for English language skills, namely listening and speaking skills, to help reduce anxiety among students applying English.